PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SD - Rahmawati; Rika Perdana, Dayu; Nuraini, Siti; Khairani, Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the low level of critical thinking skills among fifth-grade students in the Pancasila Education course at SD Negeri 1 Kalianda. This study aims to determine the effect of a project-based learning model supported by mind mapping media on students’ critical thinking skills. The research method used was a quasi-experimental design, specifically a non-equivalent control group design. The study population consisted of 54 students. The sampling technique used was saturation sampling, in which the entire population was included as the study sample. The sample in this study consisted of 54 fifth-grade students at SD Negeri 1 Kalianda, comprising 28 students in the experimental class and 26 students in the control class. Data collection was conducted through tests in the form of essay questions designed based on critical thinking ability indicators, as well as non-test methods such as observation and documentation. Data analysis was performed using a simple linear regression test, which indicated that the null hypothesis Ho was rejected and the alternative hypothesis Ha was accepted. This means that the project-based learning model supported by mind mapping media has an effect on students’ critical thinking skills in the Pancasila Education subject for fifth-grade students at SD Negeri 1 Kalianda.